Policy Implementation of Housing Financing Facilitation and Assistance for Low-Income People in Bekasi District: A Case Study of Villa Kencana Cikarang Housing - Simbolon, Adventus Managam; Rusli, Budiman; Candradewini, Candradewini (Universitas Teuku Umar, 2024)
This study aims to assess the effectiveness of housing financing facilitation and assistance policies for low-income people (LIP) in Bekasi District, with a case study of Villa Kencana Cikarang Housing. A qualitative descriptive approach with a case study design was utilized, applying Khan & Khandaker's rational model of policy implementation to evaluate five key variables: clarity of policy objectives, detailed and consistent planning, clear division of tasks, accurate standardization, and proper supervision. The findings reveal several issues, including policy targets that do not reflect the housing needs of each region, inaccuracies in targeting FLPP mortgage recipients, limited planning of FLPP credit/financing schemes, a shortage of human resources in implementing organizations, and various obstacles in post-distribution monitoring related to occupancy. Practical recommendations from this study include setting policy targets based on the proposed housing needs of each region, continuously developing and evaluating the current government housing credit/financing schemes to expand their implementation and utilization beyond LIP to include the poor and non-LIP groups, accelerating staff recruitment and rotation in implementing organizations, and ensuring inherent supervision by involving developers to monitor occupancy rates and applying strict sanctions to LIP who violate the provisions on the use of subsidized housing.